2021
DOI: 10.1111/odi.13799
|View full text |Cite
|
Sign up to set email alerts
|

Anticaries activity of GERM CLEAN in Streptococcus mutans and Candida albicans dual‐species biofilm

Abstract: Objective To evaluate the antimicrobial effects of a peptide containing novel oral spray GERM CLEAN on dual‐species biofilm formed by Streptococcus mutans and Candida albicans and to investigate whether GERM CLEAN inhibits the demineralization procedure of bovine enamel in vitro. Methods The antimicrobial effects of GERM CLEAN on dual‐species biofilm were analyzed by initial adherence rate calculation, water‐insoluble exopolysaccharides quantification, total biomass quantification, and colony‐forming units (CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
3
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 62 publications
3
3
2
Order By: Relevance
“…Moreover, the result of polarized light microscopy also supported this conclusion. It showed that the demineralization depth became shallower after the treatment of GERM CLEAN, which became deeper after the treatment of DDW, but GERM CLEAN was less effective than uoride, that is in accord with the recent study [20]. For the surface roughness, GERM CLEAN manifested a better effect than the previous study [20], which may be due to GERM CLEAN of 50% mass fraction was used and the shorter pH cycling time of the previous study, while this study used the stock solution of GERM CLEAN.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Moreover, the result of polarized light microscopy also supported this conclusion. It showed that the demineralization depth became shallower after the treatment of GERM CLEAN, which became deeper after the treatment of DDW, but GERM CLEAN was less effective than uoride, that is in accord with the recent study [20]. For the surface roughness, GERM CLEAN manifested a better effect than the previous study [20], which may be due to GERM CLEAN of 50% mass fraction was used and the shorter pH cycling time of the previous study, while this study used the stock solution of GERM CLEAN.…”
Section: Discussionsupporting
confidence: 88%
“…It showed that the demineralization depth became shallower after the treatment of GERM CLEAN, which became deeper after the treatment of DDW, but GERM CLEAN was less effective than uoride, that is in accord with the recent study [20]. For the surface roughness, GERM CLEAN manifested a better effect than the previous study [20], which may be due to GERM CLEAN of 50% mass fraction was used and the shorter pH cycling time of the previous study, while this study used the stock solution of GERM CLEAN. However, as for the lesion depth in the GC group, although it was shallower than that in the DDW group, there was no statistical difference between the two groups.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations